Creutzfeldt-Jakob disease: A great masquerade in neurology, a rare case report from South India - Sivaprakash Varadan; Sudagar Singh; Deepak Rajkumar Vangipuram; Damodharan Jayachandran (Journal of the Scientific Society, 2015)
Creutzfeldt-Jakob disease (CJD) is a rare, fatal neurodegenerative disease caused by an infectious protein called prion and is characterized by spongiform changes, neuronal loss, reactive astrocytic proliferation, and accumulation of pathologic cellular protein. Clinical presentation of CJD is characterized by rapidly progressive dementia, neurologic symptoms and visual impairment, and the development of akinetic mutism, which can mimic many neurological conditions. The diagnosis is based on clinical presentation, electroencephalogram, and typical cerebrospinal fluid and magnetic resonance imaging (MRI) findings. Literature on the incidence and prevalence of CJD is lacking in South India. We report the case of a 57-year-old woman with progressive dementia and typical neurologic symptoms, myoclonic jerks, and MRI findings of CJD. This case highlights the need for a high index of suspicion to diagnose CJD.